Front Cover: A Combined Theory‐Experiment Analysis of the Surface Species in Lithium‐Mediated NH3 Electrosynthesis (ChemElectroChem 7/2020). Issue 7 (1st April 2020) - Schwalbe, Jay A.; Statt, Michael J.; Chosy, Cullen; Singh, Aayush R.; Rohr, Brian A.; Nielander, Adam C.; Andersen, Suzanne Z.; McEnaney, Joshua M.; Baker, Jon G.; Jaramillo, Thomas F.; Norskov, Jens K.; Cargnello, Matteo
Abstract : The Front Cover shows the idealized lithium‐containing species on an electrocatalyst surface for the reduction of nitrogen to ammonia at atmospheric pressure and temperature. The nitrogen activation occurs in non‐aqueous electrolytes to achieve high faradaic efficiency on a complex reactive surface.More information can be found in the Article by J. A. Schwalbe et al .